CONSTRUCTION AND VALIDATION OF IN VITRO DOSE–RESPONSE CALIBRATION CURVE USING DICENTRIC CHROMOSOME ABERRATION. Issue 2 (20th March 2020) - Mirrezaei, Ehsan; Setayeshi, Saeed; Zakeri, Farideh; Baradaran, Samaneh
Abstract: Cytogenetic biodosimetry is a well-known method for quantifying the absorbed dose based on measuring biological radiation effects. To correlate the induced chromosomal abberrations with the absorbed dose of the individuals, a reliable dose–response calibration curve should be established. This study aimed to use frequencies and distributions of radiation-induced dicentric chromosome aberrations to develop a standard dose–response calibration curve. Peripheral blood samples taken from six male donors irradiated by an X-ray generator up to 4 Gy were studied. Three different blood samples were irradiated by known doses, then scored blindly for verification of the proposed calibration curve. Dose estimation was also carried out for three real overexposed cases. The results showed good accordance with the other published curves. The constructed dose–response curve provides a reliable tool for biological dosimetry in accidental or occupational radiation exposures.